MEMBANGUN PENGETAHUAN TEORI PERSAMAAN DIFERENSIAL TINGKAT II MELALUI METODE JIGSAW - Mudjiono; Sigit Setya Wiwaha (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
In the current reality, it is found that students are only able to memorize theories and formulas without being able to apply them. This encourages research so that students are not only able to memorize theories, but are also able to relate and apply theories and formulas to their daily problems. The Jigsaw method was developed by Elliot Aronson and his colleagues and later adopted by Slavin and his friends. In practice, students are divided into small groups consisting of 4-5 members. Each group (team) consists of heterogeneous members, both gender, race, academic ability, and other social status. Academic materials are given to groups of students in the form of text; and each student is responsible for studying a part of the text or academic material. Furthermore, each student who is responsible for a certain section gathers to form a new group called the expert group. After each student gathered in the expert group finished discussing the topic according to their section, they returned to the home team to teach other students in their group about the material that had been studied in the expert group. After meetings and discussions were held in the home group, the students were evaluated individually regarding the material that had been studied. The author's previous research with the title still has not succeeded in exceeding the minimum score of 65 out of a score of 100, because it has only reached a score of 56.20. Therefore, this research needs to be continued. After taking the action 4 times, it turned out that there was an increase in the score, even though the minimum score target (65 out of a perfect score of 100) had not been met.